Laser Pulse Phenomena and Applications - Duarte, F.J (InTechOpen, 2010)
Pulsed lasers are available in the gas, liquid, and the solid state. These lasers are also enormously versatile in their output characteristics yielding emission from very large energy pulses to very high peak-power pulses. Pulsed lasers are equally versatile in their spectral characteristics. This volume includes an impressive array of current research on pulsed laser phenomena and applications. Laser Pulse Phenomena and Applications covers a wide range of topics from laser powered orbital launchers, and laser rocket engines, to laser-matter interactions, detector and sensor laser technology, laser ablation, and biological applications.